2015
DOI: 10.1097/shk.0000000000000325
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Decreases Pulmonary–to–Systemic Vascular Resistance Ratio in a Porcine Model of Severe Hemorrhagic Shock

Abstract: Vasopressors are gaining renewed interest as treatment adjuncts in hemorrhagic shock. The ideal vasoconstrictor will increase systemic blood pressure without increasing pulmonary vascular resistance (PVR), which hinders pulmonary perfusion and exacerbates hypoxemia. However, the selectivity of pressors for pulmonary versus systemic vasoconstriction during hemorrhage has not been characterized. The purpose of this study was to test the hypothesis that vasopressin (VP) has distinct effects on pulmonary versus sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…However, the addition of vasopressin had no effect on this parameter in either group, during either normoxic or hypoxic ventilation. These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the addition of vasopressin had no effect on this parameter in either group, during either normoxic or hypoxic ventilation. These data are in accord with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin‐induced decrease in the pulmonary‐to‐systemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation . Vasopressin may be unique among pressors in having no pulmonary constrictor effect, but we concur that it has no apparent pulmonary vasodilator effect .…”
Section: Discussionsupporting
confidence: 91%
“…However, we cannot provide evidence for any increase in with recent studies of vasopressin in pulmonary hypertension that, while noting a vasopressin-induced decrease in the pulmonary-tosystemic pressure ratio, ascribe this improvement to a rise in aortic pressure rather to pulmonary vasodilation. 42,43 Vasopressin may be unique among pressors in having no pulmonary constrictor effect, 44 but we concur that it has no apparent pulmonary vasodilator effect. 45 Indirect vasodilation has been postulated, for example, through vasopressin-induced release of atrial natriuretic peptide 39 ; but these effects would fall outside of the timeframe of the present study.…”
Section: Avpr1a Expression In Aorta Was Attenuated In Pphn Animals Cmentioning
confidence: 66%
“…Persistent pulmonary hypertension contributes to worsening hypoxemia in endotoxic shock. We previously showed that vasopressin spares the pulmonary vasculature of its potent vasoconstrictive action [21], thus it was not surprising to see that when vasopressin and dopamine were used in conjunction with ECMO that the elevated pulmonary to systemic vascular resistance ratio (PVR/SVR) caused by ET returned to baseline. Because oxygen delivery was already increased with ECMO alone, the relative vasoconstrictive sparing of the pulmonary bed did not contribute additional systemic oxygen delivery gains.…”
Section: Discussionmentioning
confidence: 99%
“…AVP is a nonsympathomimetic vasopressor, which causes vasoconstriction via activation of the V 1 vasopressin receptor [ 11 ]. In vitro and in vivo studies have demonstrated that AVP produces systemic vasoconstriction with relatively fewer effects on the pulmonary circulation; such combined effects produce a desirable decrease in the pulmonary vascular resistance/systemic vascular resistance ratio [ 12 14 ]. This AVP-mediated selective vasoconstriction of the systemic vessels has also been shown in several clinical studies in patients undergoing cardiac surgery [ 4 6 ].…”
Section: Case Presentationmentioning
confidence: 99%